What drives the use of natural products for medicinal purposes in the context of cultural pluralism? - Muniz de Medeiros, Patrícia (2016)
Introduction: What are the drivers of health seeking behaviors in a culturally diverse scenario? A context of medical and cultural pluralism with native and migrant people in NE Brazil was chosen to study the use of complementary and alternative medicine (CAM) and official medicine (OM) products and their drivers. Methods: A one-year therapeutic recall was used to obtain information on individual health problems, products to treat their problems and access to health services. A generalized linear model (GLM (binomial errors) was employed to indicate the variables that better explained therapeutic choices. Results: Most people use both CAM and OM products and most illnesses are treated by both systems. The GLM indicated that women, migrants and people that turns to primary health-care services (PHCs) in a lower extent are more likely to exclusively chose CAM products and are also more likely to prioritize them. Frequentation of the local health center also leads to a proportionally higher use of CAM products than the frequentation of other PHCs from the surroundings. Conclusions: Women, migrants and people that do not frequent PHCs are the main supporters of CAM products. In the case of migrant people, their high adhesion to CAM products (especially medicinal plants) can turn them into new depositors of local (traditional) knowledge, although this knowledge will not be dissoluble from other types of medicinal plant knowledge.